Tourism Law Enforcement in Regional Spatial Planning and Licensing Perspectives - Haris Budiman; Suwari Akhmaddhian; Dela Agustin; Rahul Bhandari (UNIFIKASI : Jurnal Ilmu Hukum, 2023)
The increasing development of the tourism sector in Kuningan Regency reflects the progress and development of the area. By looking at the licensing and spatial planning perspectives, a study on the development of the tourism sector in Kuningan Regency is needed. Hence, this study aims to analyze tourism licensing mechanism and tourism law enforcement concerning spatial planning and licensing in Kuningan Regency. This study applied an empirical juridical research method in which the primary and secondary data used were collected through interviews, observation, and literature study. As result, it was found that the licensing mechanism for tourism development in Kuningan Regency is divided into two categories, namely licensing carried out at the Investment Agency and One-Stop Integrated Service and the Gunung Ciremai National Park Office. It is because Kuningan Regency has an area included in the National Park zone, so the licensing process should directly go to the Ministry of Environment and Forestry. Preventive law enforcement efforts have been carried out by law enforcement officers, including drafting legal opinions, holding meetings, as well as avoiding violations during the licensing process. Thus, it can be concluded that the policy and the implementation of law enforcement in the licensing and spatial planning for tourism development in Kuningan Regency are carried out well by the Regional Government and law enforcement officers. Yet, a renewal on Kuningan Regency Regional Regulation on a Detailed Spatial Planning as a basis for determining licenses is needed.